ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN RUMAH TANGGA DI KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Rina Nasmiwati; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to analyze the influence of the level of education, type of work, level of health, number of dependents, ana mental/spiritual attitudes towards poverty of households in the Bayang sub-district of Pesisir Selatan district. The type of research is descriptive and quantitative research. The population of this study is poor households in the Bayang sub-district of Pesisir Sealatan district. The sample was determined based on cluster sampling technique, which was obtained through 42 respondents. This study uses multiple linear regression analysis. The results of this study indicate that (1) the level of education has a positive and insignificant effect on poverty of households in the Bayang sub-district Pesisir Selatan district, (2) the type of work has a positive and insignificant effect on poverty of households in the Bayang sub-district Pesisir Selatan district, (3) level health has a positive and insignificant effect on poverty of households in Bayang sub-district Pesisir Selatan district, (4) the number of dependents has a positive and significant effect on poverty of households in Bayang sub-district Pesisir Selatan district, (5) mental/spiritual attitudes have a positive and insignificant effect on poverty of households in Bayang sub-district Pesisir Selatan district, (6) together there is a positive and significant effect on poverty of households in Bayang subdistrict Pesisr Selatan district.